Risk and incidence of fatal adverse events associated with immune checkpoint inhibitors: a systematic review and meta-analysis - Jiang Y; Zhang N; Pang H; Gao X; Zhang H (Dove Medical Press, 2019)
Yi Jiang,1 Ning Zhang,1 Hailin Pang,1 Xiaobo Gao,2 Helong Zhang1,3 1Department of Oncology, Tangdu Hospital, Air Force Military Medical University, Xi’an, Shan’xi, China; 2Department of Medicine, Tangdu Hospital, Air Force Military Medical University, Xi’an, Shan’xi, China; 3Institute of Cancer, Air Force Military Medical University, Xi’an, Shan’xi, China Background: Given the increasing use of immune checkpoint inhibitors (ICIs), a concomitant rise in adverse events is inevitable. In a recent Phase III trial of ICIs versus placebo, we found the staggering difference of incidence of fatal adverse events (FAEs). Hence, we should determine the risk of FAEs in ICIs. Objective: To address the risks of FAEs associated with each ICI regimen, we performed a systematic review and meta-analysis of clinical trials with the Food and Drug Administration-approved ICI regimens in patients with advanced solid tumors. Methods: Literature searching was based on PubMed before April 15, 2018. The numbers of FAEs in both study group and placebo group were collected. We assessed the risk of fatal adverse reactions associated with ICIs on Pooled Peto OR and associated 95% CI. Results: Twelve trials were identified. OR value of FADs in all ICIs was 2.32 (95% CI: 1.33, 4.05; P=0.003). The incidence of FAE in ICI in all included studies were up to 3.2%. OR value of clinical trials of prostate cancer was 3.71 (95% CI: 1.12, 12.26; P=0.03). Among the ICI cohorts, the common FAEs were gastrointestinal toxicity (n=12, 25%), pulmonary toxicity (n=10, 20%), cardiac toxicity (n=5, 10%), and hepatic toxicity (n=5, 10%). Conclusion: The cytotoxic T-lymphocyte-associated protein-4 (CTLA-4) inhibitors have a significantly higher risk of FAE (P=0.01), whereas programmed cell death protein 1 (PD-1) inhibitors were not. The most common CTLA-4-related FAE was gastrointestinal toxicity, and the most common PD-1-related FAE was pulmonary toxicity. Moreover, we have shown that ipilimumab has significant dose-dependent lethal toxicity. Keywords: treatment-related mortality, immune mediated death, immune mediated mortality